Mental Image in Kindergarten Children's Drawings - Alsaggar, Mowafaq Ali; Fakhrou, Abdulnaser (Dirasat: Educational Sciences, 2020)
The purpose of the study was to identify the influences of the surrounding environment on kindergarten children's drawing and their inner expressions of surrounding things, phenomena and events as being detached from the actual use of sensations. In doing so, the researchers conducted a study at Model School affiliated to Yarmouk University, Irbid- Jordan in the school year 2017/2018. The sample of the study was (12) kindergarten children in the age group (4-5). At the completion of content analysis of the drawings, it was found that (4-5) kindergarten children’s drawings were highly influenced by their surrounding environment as this was evident by the different expressions used in the drawings, which were diversified, mirror the place where they live such as in the case when one of the children drew rural features, while another was mainly concerned with drawing cars. Some figures were more common than others, indicating that children recognize something well and can easily be visually represented (e.g. the sun, house, window, flower, book, ball) by them. Children preferred drawing figures they are familiar with which they already drew. Finally, the study concluded that some of the children's drawings were ambiguous and cannot be recognized unless the child explains them.